2019
DOI: 10.1002/adfm.201907120
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically Derived Graphene‐Like Carbon Film as a Superb Substrate for High‐Performance Aqueous Zn‐Ion Batteries

Abstract: 3D graphene, as a light substrate for active loadings, is essential to achieve high energy density for aqueous Zn-ion batteries, yet traditional synthesis routes are inefficient with high energy consumption. Reported here is a simplified procedure to transform the raw graphite paper directly into the graphene-like carbon film (GCF). The electrochemically derived GCF contains a 2D-3D hybrid network with interconnected graphene sheets, and offers a highly porous structure. To realize high energy density, the Na:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 49 publications
2
56
0
Order By: Relevance
“…The maximum energy and power density of other similar recent works reporting on high performance Zn//MnO 2 battery systems were also included in the plot for comparison against our Zn//O dc À MnO 2 battery system. [17,29,40] As observed from the plot, the Zn// O dc À MnO 2 battery system in our work managed to achieve comparable and even better performance than the other Zn// MnO 2 battery systems.…”
Section: Resultssupporting
confidence: 62%
“…The maximum energy and power density of other similar recent works reporting on high performance Zn//MnO 2 battery systems were also included in the plot for comparison against our Zn//O dc À MnO 2 battery system. [17,29,40] As observed from the plot, the Zn// O dc À MnO 2 battery system in our work managed to achieve comparable and even better performance than the other Zn// MnO 2 battery systems.…”
Section: Resultssupporting
confidence: 62%
“…[282] When summarizing previous works providing the parameter of cathode loading mass, it is apparent to note that the majority of laboratory studies showed low areal capacities of less than 0.3 mAh cm −2 , and the areal current varies from 1 to 12 mA cm −2 (Figure 25). [33,79,80,94,96,280,[283][284][285][286][287][288][289] These areal capacities are extremely low for powering customer electronics. [122] Rather than numerically refreshing the cycling life in laboratory, evaluating the diverse methods of dendrite protection under practical conditions moves toward the realization of dendrite-free Zn metal batteries.…”
Section: Areal Capacity and Current Densitymentioning
confidence: 99%
“…Typically, AZIBs consist of an intercalation-type cathode, a zinc metal anode and a Zn 2+ -based aqueous electrolyte, which demonstrate attractive features of large theoretical capacity (820 mA h g −1 and 5855 mA h cm −3 ), wide working potential window (0-2 V), reversible plating/stripping of Zn, high safety, environmental friendliness, low cost and facile manufacturing process [1][2][3][4]. Since Kang's group [5] [6][7][8][9]. Among them, the α-MnO 2 -based AZIBs exhibit the highest specific capacity of more than 380 mA h g −1 , long-term reversibility and extraordinary rate capability, which benefit from their 2×2 tunnel structure with corner-sharing double MnO 6 octahedra chains [10].…”
Section: Introductionmentioning
confidence: 99%